How Does Banking Diversity Fit in the General Vision Inspiring the Joint Process of Banking Union and Capital Markets Union? - Giovanni Ferri; Doris Neuberger (Vierteljahrshefte zur Wirtschaftsforschung, 2018)
The Global Financial Crisis (GFC: 2008–2009) and the Euro Sovereign Crisis (ESC: 2010–2012) seem a process of creative destruction for the European Union (EU). The huge damage provoked by the GFC and ESC was, in fact, followed by important institutional building steps as the Banking Union (BU) and Capital Markets Union (CMU). Their swift introduction suggests that BU and CMU arrived as emergency solutions. With hindsight we may now reassess them. We posit that two unintended side-effects materialised: 1) CMU twisted the balance against banking and in favour of financial markets; 2) BU is, de facto, weakening banking diversity. Thus, even if CMU and BU were successful at reaching EU's economic goals, their side-effects impair the social and cultural goals equally enshrined in EU treaties. We argue that CMU and BU should be revised to limit the damage to social and cultural goals or, else, other EU policies should be devised to restore the balance. – – Die globale Finanzkrise (GFC: 2008–2009) und die Euro-Staatsschuldenkrise (ESC: 2010–2012) scheinen ein Prozess der kreativen Zerstörung für die Europäische Union (EU) zu sein. Den enormen Schäden, die durch die GFC und ESC verursacht wurden, folgten in der Tat wichtige institutionelle Aufbauschritte wie die Bankenunion (BU) und die Kapitalmarktunion (CMU). Ihre schnelle Einführung deutet darauf hin, dass BU und CMU als Notfalllösungen zum Einsatz kamen. Im Nachhinein können wir sie nun neu bewerten. Wir gehen davon aus, dass zwei unbeabsichtigte Nebeneffekte eingetreten sind: 1) Die CMU hat das Gleichgewicht gegen das Bankwesen und zugunsten der Finanzmärkte verschoben; 2) die BU schwächt de facto die Bankenvielfalt. Selbst wenn es CMU und BU gelungen ist, die wirtschaftlichen Ziele der EU zu erreichen, beeinträchtigen ihre Nebenwirkungen die sozialen und kulturellen Ziele, die gleichermaßen in den EU-Verträgen verankert sind. Wir argumentieren, dass CMU und BU überarbeitet werden sollten, um den Schaden für soziale und kulturelle Ziele zu begrenzen, oder dass andere EU-Politiken entwickelt werden sollten, um das Gleichgewicht wiederherzustellen.
Keywords: F36; G15; G18; G21; G28; 330; Banking diversity; Capital Markets Union; Banking Union; relationship banking; shareholder banks; stakeholder banks